ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN MINAT BELAJAR SISWA MTS - Siti Nurjanah; Siti Sarah; Luvy Sylviana Zanthy (Journal on Education, 2019)
In this study the authors analyzed the difficulties of students in the process of the ability of mathematical creative thinking skills and to determine student learning interest in each item statement. Based on the analysis, for the material the straight Equation error made by students in working on creative thinking questions is the mastery of the concept of the material resulting in 67.63% of 34 creative students. The question instrument used is a question that has been tested for reliability, validity, differential power and difficulty index has also been validated by an expert validator. The interest in studying junior high school students is only reaching 59.20% in straight line equations. The indicator of student interest in learning gained the smallest percentage of 56.09% so that it influenced other indicators. The research method uses descriptive qualitative analysis to find out in depth the achievement of indicators of creative thinking skills and mathematical learning interest in each item statement. Based on the results of the overall research that the achievement of indicators of the ability to think creatively and the learning interest of students is still low.